Pengaruh Integrasi E-Book Interaktif pada Kegiatan Belajar Mengajar Sains - Fransiska Astri Kusumastuti (Bina Nusantara University, 2020)
This study aims to see the effectiveness of the use of interactive e-book on student performance. Other than that, this study also discusses the integrating of interactive e-book into science learning activity, so that it can provide learning evaluation as material for e-book development in future studies. This study conducted in quasi-experimental pre-test post-test control group design. 88 students that are involved in this study were selected randomly of two classes from eight classes, and grouped into experiment and control class to see the effectiveness of using interactive e-book in science learning activities. Independent t-test was used to find out the effectiveness of the interactive e-books, and questionnaire was used to see student perceptions of interactive e-book that have been used in the science learning activity. From the Wilcoxon test, found that probability value (p)obtained was 0.000 (p<0.05). This result showed that each class showed significant difference in learning outcomes, where the experimental class get better than the control class. This finding also supported by the results of the questionnaire that students in experimental class has better learning experiences than students in control class.